Nazism som forskningsobjekt - Ambjörnsson, Ronny; Berggren, Lena; Ehn, Billy; Ehn Knobblock, Inger; Ericsson, Tom; Fruitman, Stephen; Frånberg, Per; Högberg, Ulf; Liliequist, Jonas; Liliequist, Marianne; Norrhem, Svante (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
How is research and teaching on Nazism best conducted? Despite the nearly universal condemnation of an unsanctioned "lecture" by a member of a Swedish Nazi party held at Umeå University in December 1997, a number of complex questions have been raised about the role of the researcher and the research object, as well as about the qualitative difference between conducting thorough-going research into Nazism, past and present, and allowing Nazi ideologies to penetrate the universities. An important way of countering the latter is to do more research into Nazism and the Holocaust and produce better, more accessible presentations of the wealth of research already extant. Insight into the nature and essence of Neo-Nazi ideology can hardly be expected to be won through highly-censored and propagandistic "lectures", but rather by closely studying the undergrowth of Nazi rhetoric and White Power music, the internal jargon and propaganda directed toward sympathizers and prospective members. It would be a fateful mistake to try and ignore Nazism, but neither can an open discussion be conducted on its own conditions. Recurring conferences and symposia and interdisciplinary efforts at designing improved study courses on Nazism are important contributions to maintaining the very fundament of our society which these movements reject — the equal rights of all mankind.